Adaptive and Responsive School Leadership: A Strategy for Improving Educational Quality in the Glocalization Era - Hanum, Nur Amaliyah (Universitas Trunojoyo Madura, 2025)
Principals are faced with various complex problems in improving the quality of sustainable education in the era of glocalization, so it is necessary to implement adaptive and responsive leadership strategies in educational institutions. This study aims to describe several adaptive and responsive leadership strategies of principals in improving the quality of education in the era of glocalization. The method used in this study is a literature review study with thematic data analysis. The results of the study explain that the adaptive and responsive leadership of a principal has several ways to improve the quality of education in the era of glocalization, namely through (1) curriculum glocalization, (2) improving the quality of human resources, (3) strengthening character and culture, and (4) learning innovation. So the adaptive and responsive leadership of the principal can make the school curriculum more relevant to the needs of the world of work, human resources more professional and competent, school culture and character stronger, and learning more innovative and enjoyable. So that synergistically able to improve the quality of schools in a sustainable manner through graduates who are ready to compete internationally but have local culture and character.